Dexter is dead [large type] : a novel - Lindsay, Jeffry P. (Center Point Large Print, 2015)
"Dexter faces a murder charge for a crime he did not commit. His only chance for freedom lies with his brother, Brian, who has a dark plan to prove Dexter's innocence. But the stakes are deadly, and the epic showdown that lies in Dexter's path may lead, once and for all, to his demise"--